2019
DOI: 10.1063/1.5094472
|View full text |Cite
|
Sign up to set email alerts
|

Degradation analysis of 1 MeV electron and 3 MeV proton irradiated InGaAs single junction solar cell

Abstract: In this paper we reported the electrical and spectral properties of 1 MeV electron and 3 MeV proton irradiated In0.53Ga0.47As single junction solar cell, which is used as the fourth subcell of wafer bonded GaInP/GaAs//InGaAsP/InGaAs four-junction full spectra solar cell. The equivalent displacement damage dose model was applied to study the radiation effects of solar cell. The results show that the electrical parameters of the solar cell degrade seriously with the increase of irradiation fluences, the reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Si and Be were used as the n-type and p-type doping source, respectively. A detailed description for the growth and fabrication process of this solar cell has been reported in our previous work [15]. All tested samples are 2.5 × 2.5 mm 2 in size and have an initial conversion efficiency of around 11% under the standard AM0 spectra (136.7 mW/cm 2 at 25°C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Si and Be were used as the n-type and p-type doping source, respectively. A detailed description for the growth and fabrication process of this solar cell has been reported in our previous work [15]. All tested samples are 2.5 × 2.5 mm 2 in size and have an initial conversion efficiency of around 11% under the standard AM0 spectra (136.7 mW/cm 2 at 25°C).…”
Section: Methodsmentioning
confidence: 99%
“…Karlina et al [14] investigated the 3/10 MeV proton and 1 MeV electron radiation effects of InP/InGaAs solar cells and indicated that InGaAs is an optimum candidate for InP/InGaAs triple-junction solar cells to improve the efficiency. In our previous work, the radiation damage of 3 MeV electron and 1 MeV proton-irradiated In 0.53 Ga 0.47 As single cells was well studied and we concluded that the major degradation of spectral response (EQE) usually occurs in the long wave region [15].…”
mentioning
confidence: 95%
“…Azınlık taşıyıcısı yeniden birleşme merkezleri, güneş hücresinin foton soğurması sonucunda oluşan elektronların ve deşiklerin yeniden birleşmesine neden olurlar. Bu durum, p-n ekleminin taban katmanındaki (base layer) azınlık yük taşıyıcılarının azalmasına neden olduğu için güneş hücresinin çıkış performansının kötüleşmesi ile sonuçlanır [12][13][14]. Diğer taraftan, çoğunluk yük taşıyıcısı tuzak merkezleri, çoğunluk yük taşıyıcılarını yakalayarak (n-tipi bölgede elektronlar, p-tipi bölgede deşikler) malzemenin iletkenliğinin azalmasına neden olur [15].…”
Section: Gi̇ri̇ş (Introduction)unclassified